Coupled CAD-CFD automated optimization for leading and trailing edge of an axial impulse turbine blade. (1st October 2020) - Halder, Paresh; Kumar, P. Madhan
Abstract: A bidirectional impulse turbine with fixed guide vanes is used in an oscillating water column to extract wave energy. The turbine suffers from low aerodynamic efficiency, and it is required to improve performance. In the present study, coupled CAD-CFD automated optimization of the blade leading and trailing edge ratio was performed to maximize the efficiency. The design points were generated using a central composite design sampling technique and response surface optimization method estimated the optimum design. The optimization pipeline was automated using the Ansys Design Exploration module. Ansys Turbo Grid was used for generating structured hexahedral elements in the computational domain, and the problem was solved in Ansys CFX® v16.2. The results showed that the modified leading and trailing edge enhanced the performance compared to the reference blade by minimizing the pressure drop. The optimized design improved the relative peak efficiency and torque by 3.4% and 2% respectively. Additionally, a detailed flow analysis has been reported in this paper. Highlights: A coupled CAD-CFD fully automated optimization approach was developed and implemented. Relative peak efficiency and torque coefficient were enhanced by 3.4% and 2% respectively, in the optimized design. Optimizing the blade leading and trailing edge improves the turbine performance.